Study of the Copper Corrosion Mechanism in the Presence of Propionic Acid Vapors (2009)
The interaction mechanism between copper and propionic acid vapors is shown. Exposures were carried out to various pollutant concentrations and times. Cathodic scan, x-ray diffraction (XRD) and scanning electrode microscope (SEM) were used to quantify the degree of deterioration. The results obtained were explained by the following mechanism: A cuprite (Cu2O) layer covers the copper surface immediately; this compound in presence of adsorbed water is oxidized to tenorite (CuO). The hydration of the tenorite layer benefits the formation of a hydroxide compound such as CuO xH2O. As the pollutant level is increased, insoluble basic propionate is formed (Cu(OH)x(CH3CH2 COO)2-x). Higher concentrations of propionic acid acidify the monolayers and a new compound Cu(CH3CH2COO)2 H 2O begins to precipitate at low pH, this is the main constituent of the green olive patina formed under these conditions. This mechanism agrees, in general terms, with those proposed in previous works to study the interaction between copper and the acetic and formic acids.